Hair sheep in the Americas: economic traits and sustainable production - Dearborn, Lindsey; Abdul-Rahmaan, Bakeerah; Pesato, Michael; Memili, Erdogan; Rios, Leyla (Frontiers in Animal Science, 2023)
The relevance of hair sheep and their place in animal agriculture in the United States is expanding. Fueled by the exigency of sustainable agricultural practices, the integration of hair sheep to replace their wool breed counterparts is essential. Approximately 10 % of all sheep globally are hair sheep but they are growing in numbers and production each year. Hair sheep breeds are widely diverse but share a common origin in tropical countries. Most of the prominent breeds were mindfully developed and crossed with wool breeds (namely, the Mouflon sheep) to improve the economically important traits of the animal. This genetic development has proven successful; hair sheep are considered highly advantageous in carcass quality, meat taste, litter size, and leather quality. Aside from those economically important traits, hair sheep are also advantageous in production traits, such as parasitic resistance, disease resistance, heat tolerance, sperm quality, and nutritional efficiency. These identified traits of hair sheep are highly desirable and contribute to the hair sheep's positive reputation. However, hair sheep pose some disadvantages, such as an average or below average scrotal circumference, lower meat yield (although high in quality), meat with higher cholesterol than that of the wool breeds, and the lack of wool leaving the hair sheep susceptible to cold stress. These disadvantages can be mitigated with genetic selection and production techniques. The importance to further developing hair sheep is irrefutable. This review focuses on the fundamental and applied science of the most common hair sheep breeds and is expected to be useful for students, scientists, and producers of hair sheep.Commented [RdAL1]: REVIEWER 3: Graphic elements with tables must be inserted to improve the discussion. And this was not clearly addressed or discussed. The article is not very informative and very informative; therefore, we believe it needs to be greatly improved, balanced, comprehensive, and critical view of the research area. Relevant literature needs to be significantly improved.